Effect of Charcoal Toothpastes on the Color Stability of Nano-Filled Composites - Prathiksha Shetty; Pavitra Sampath B; Prabhu Varsha; Karkala Venkappa Kishan; Soumya T E; Naik Navnith Shiva (RGUHS Journal of Dental Sciences)
Objectives This study aimed to ascertain the impact of charcoal toothpastes on the colour stability of resin composites loaded with nanoparticles.Methods Thiry disc-shaped specimens were made utilizing a mould of 8 mm diameter and 2 mm thickness. Fifteen samples each were made for both bulk-fill Tetric-N-Ceram as well as nano-filled composite resins Z250 Filtek Z250 XT all in A3 shade. Then three sets of ten discs each were created from the samples and were exposed to brushing with three toothpastes-Healthvit activated charcoal Colgate total charcoal deep clean Colgate total control. A reflectance spectrophotometer was utilized for assessing colour stability. The data were statistically analysed using the Shapiro Wilks test ANOVA and paired t-test.Results Among the toothpastes Colgate total charcoal deep clean showed greater colour shift in the groups whereas Healthvit activated charcoal toothpaste showed the least colour change.Conclusion The resilience of resin composites colour was affected by the dentifrice utilised. Tetric N Ceram demonstrated decreased colour stability both before and after exposure to dentifrices. In comparison to Healthvit activated charcoal toothpaste Colgate charcoal toothpaste exhibited lowest colour retention capacity.